Association analysis of PAEP, KRT10, and BMP7 genes SNPs with reproductive traits in Kele pigs. - Yong Zhao; Chunyuan Wang; Yan Wu; Jin Xiang; Yiyu Zhang (PLoS ONE, 2025)
This study aimed to investigate the effects of single nucleotide polymorphisms (SNPs) in progestogen-associated endometrial protein (PAEP), keratin 10 (KRT10), and bone morphogenetic protein 7 (BMP7) genes on reproductive traits (total number of piglets born, number of piglets born alive, litter birth weight, number of piglets weaned and litter weight weaned) in Kele pigs. We used 255 multiparous Kele sow (2-4 parities) as research materials. SNPs were identified by using a PCR amplification instrument and sequence alignment software DANMAN. The population genetic characteristics of SNPs were analyzed using the SHEsis online software. Bioinformatics analyses of SNPs were conducted using RNAfold, SOPMA, SWISS-MODEL, and Swiss-PdbViewer programs. The associations between the SNPs and reproductive traits in Kele pigs were analyzed through SPSS 22.0 software. In this study, nine SNPs were identified in the three genes: g.1884992 T > C (exon 4), g.1885125 G > C (intron 4), and g.1885158 G > A (intron 4) in PAEP, g.21643703 C > T (intron 4), g.21643714 G > A (intron 4) and g.21643741 G > A (exon 5) in KRT10, and g.57647887 G > A (intron 3), g.57647990 C > T (intron 3) and g.57648145 C > G (intron 3) in BMP7. In SNPs g.1884992 T > C of PAEP, missense mutation eventuated structural changes in mRNA and proteins' secondary structure. In SNPs g.21643741 G > A of KRT10, the synonymous mutation led to an alteration in mRNA secondary structure. For PAEP, the CC genotype in SNPs g.1885125 G > C and the AA genotype in SNPs g.1885158 G > A showed significantly higher values than other genotypes in all reproduction traits except for litter birth weight, preliminarily identified as the favorable genotypes. For KRT10, the GG genotype in SNPs g.21648641 G > A showed significant superiority to the AA genotype (P < 0.05) in all aspects except for litter birth weight and notably surpassed the GA genotype in the total number of piglets born (P < 0.05), preliminarily recognized as a favorable genotype. Regarding BMP7, the GA genotype in SNPs g.57647887 G > A and the CT genotype in SNPs g.57647990 C > T exhibited significantly higher number of piglets born alive and number of piglets born alive compared to other genotypes (P < 0.05). The GG genotype in SNPs g.57648145 C > G was significantly associated with higher litter birth weight (P < 0.05). The result of diplotype analyses indicated that the H3H3 (CCGGGG) of PAEP and H3H3 (CCGGAA) of KRT10 had a significant effect on the five traits. For BMP7, the H4H4 (AATTGG) diplotype showed a significant influence on all genotypes except litter birth weight.